Penerapan Penggunaan Dongkrak Ulir Elektrik Jack Sebagai Media Kompetensi Pembelajaran Sistem Hidraulik Di SMK Ma’arif NU Talang - Amin Nur Akhmadi; M. Taufik Qurohman; Mukhamad Khumaidi Usman (Madani : Indonesian Journal of Civil Society, 2020)
Vocational High Schools are the biggest contributor to unemployment in the area, many supporting factors such as the unstable state of the company. Basically that's not all, the teaching process at the Vocational School is at the forefront of increasing unemployment rates for SMK graduates. From the results of community service activities the following conclusions with the existence of community service activities at SMK Ma'arif Nu Talaang, Tegal Regency, it provides knowledge, understanding and innovation of efficient power transfer system equipment in accordance with Operational Procedures for Safety Procedures. Speed up the work when practicing lifting a car to change tires in the subjects of the power transfer system competency with the SOP equipment so as to make students competent in their performance practices